ANO7: Insights into topology, function, and potential applications as a biomarker and immunotherapy target. (October 2021) - Guo, Jian; Wang, Dan; Dong, Yuan; Gao, Xiang; Tong, Haibin; Liu, Wei; Zhang, Lei; Sun, Meiyan
Highlights: A dual-function transmembrane protein working as both ion channel and lipid scramblase. Restricted expression in normal and cancerous prostate tissues. The expression level was significantly inversely associated with the Gleason scores of PCa. A potential biomarker for diagnosis and prognosis of PCa; a valuable target for immunotherapy against PCa. Abstract: Anoctamin 7 (ANO7) is a member of the transmembrane protein TMEM16 family. It has a conservative topology similar to other members in this family, such as the typical eight-transmembrane domain, but it also has unique features. Although the ion channel role of ANO7 has been well accepted, evolutionary analyses and relevant studies suggest that ANO7 may be a multi-facet protein in function. Studies have shown that ANO7 may also function as a scramblase. ANO7 is highly expressed in prostate cancer as well as normal prostate tissues. A considerable amount of evidence has confirmed that ANO7 is associated with human physiology and pathology, particularly with the development of prostate cancer, which makes ANO7 a good candidate as a diagnostic and prognostic biomarker. In addition, ANO7 may be a potential target for prostate cancer immunotherapy. Antibody-based or T cell-mediated immunotherapies against prostate cancer by targeting ANO7 have been highly anticipated. ANO7 may also correlate with several other types of cancers or diseases, where further studies are warranted.